(untitled) (JURNAL ADMINISTRASI PUBLIK, 2018)
ABSTRAK: Public Service is any activity in the framework of fulfillment of basic needs in accordance with the basic rights of every citizen or resident of an item, service and administrative service provided by the service providers related to the public interest. Examples of public services in the form of administrative services namely the making of Domicile Letters, Birth Certificates, and Purchase Deed Certificate, services in the form of services such as post office and bank. While services in the form of goods such as tax payments used for the construction of state infrastructure such as bridges and highways. Quality of service is a condition where created a dynamic relationship between users and service providers, good service, human. Public service is closely related to the ability, responsiveness, timeliness, and available infrastructure. If the services provided are in accordance with the expected by service users, it can be said that service is a quality service. Conversely, if the services provided are not in accordance with the expectations of service users, it can be said that the service is not qualified. Good service quality is not based on the perspective or perception of service providers but rather based on consumer perceptions and rules or provisions about the quality of service. Kata kunci: Quality, Public Service, sub-District Government